Analysis of the Influence of the Halal Industry on Indonesia's Economic Growth - Destriyansah, Wahyu; Imsar, Imsar; Harahap, Muhammad Ikhsan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The aim of this research is to examine how the halal industry, including halal food, halal clothing, halal medicine and cosmetics, halal travel and tourism, halal media and recreation and halal finance, influences Indonesia's economic growth. This research uses quantitative techniques using multiple linear regression. The data used comes from 2015-2021 and is interpolated monthly. The research results show that halal food and halal clothing partially have a positive and significant effect on Indonesia's economic growth; on the contrary, halal pharmaceuticals and cosmetics, halal travel and tourism, and halal finance have a negative and significant influence on Indonesia's economic growth; then Halal Media and Entertainment has no effect. Simultaneously, research shows that Indonesia's economic growth is influenced by halal food, halal clothing, halal pharmaceuticals and cosmetics, halal travel and tourism, halal media and recreation, and halal finance.